Association of β1-, β2-Adrenoceptor and LGALS-3 Genes Polymorphisms with the Course of Heart Failure in Patients with Ischemic Heart Disease - Nadiia M. Kulaiets (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To study the relationship between β1-, β2-adrenoceptor (β-AR) and LGALS-3 genes polymorphisms with the course of heart failure (HF) in patients with coronary heart disease.Materials and methods. We examined 201 patients with HF on the background of post-infarction cardiosclerosis. Control group included 43 healthy individuals of comparable age and sex. Genotyping was carried out for 4 polymorphisms (rs1801253 and rs1801252 of the β1-AR gene; rs1042714 of the β2-AR gene and rs2274273 of the LGALS-3 gene). Statistical analysis was performed using Statistica 10.0 and SNPStats programs.Results. In patients with HF, the A allele (A/G-A/A) of the rs1801252 polymorphism of the β1-AR was associated with a reduced risk of rehospitalization (RH) within a year (odds ratio [OR] = 0.44 [0.20-0 .98], p = 0.036, dominant inheritance model). The data on the reduction of the risk of RH in patients with HF in the presence of the A allele of the rs1801252 polymorphism of the β1-AR gene were also confirmed in the log-additive (OR = 0.44 [0.20-0.96], p = 0.027) and, mainly, in excessively dominant (OR = 0.48 [0.21-1.06], p = 0.059) inheritance models. The analysis showed a higher frequency of allele A of the rs1801252 polymorphism of the β1-AR gene in the group of patients with HF who did not have RH due to decompensation during the year, compared to patients with RH (14.9% versus 7.0%, respectively; χ2 = 4.304; p = 0.039). The A allele of the specified gene polymorphism was also associated with a reduced risk of persistent atrial fibrillation (AF) (OR = 0.34 [0.14-0.84], p = 0.018, dominant inheritance model). This regularity was confirmed in the overdominant (OR = 0.27 [0.11-0.69], p = 0.0048) and in the codominant (OR = 0.28 [0.11-0.72], p = 0.0081) inheritance models. The A allele (A/G-A/A) of the rs2274273 polymorphism of the LGALS-3 gene was associated with an increased risk of AF in patients with HF (OR = 6.63 [1.31-33.53], p = 0.032, codominant inheritance model). Data on the increase in the risk of AF, provided that the A allele of the aforementioned polymorphism is present, were also confirmed in the recessive (OR = 5.12 [1.08-24.24], p = 0.017) and log-additive (OR = 2.11 [1.13-3.94], p = 0.015) inheritance models. The risk of RH in patients with HF and concomitant diabetes mellitus increased in patients with heterozygous (G/C) polymorphism rs1801253 of the β1-AR gene (OR = 3.91 [1.03-14.87], p = 0.0041).Conclusions. The course of HF was associated with genetic differences β1-AR, in particular: the A allele of the rs1801252 polymorphism of the specified gene reduced the risk of RH within a year (14.1 % vs. 27.0 %; OR = 0.44; p = 0.036, dominant inheritance model) and AF (18.3 % vs. 39.5 %; OR = 0.34; p = 0.018, dominant inheritance model). The risk of RH of patients with HF and accompanying diabetes mellitus was higher with heterozygous (G/C) rs1801253 polymorphism of the β1-AR gene (24.4 % vs. 11.1 %; OR = 3.91; p = 0.0041). The A allele of the rs2274273 polymorphism of the LGALS-3 gene was associated with an increased risk of AF in patients with HF (20.0 % vs. 4.7%; OR = 6.63, p = 0.032, codominant inheritance model). No probable association of the rs1042714 polymorphism of the β2-AR gene with the course of HF was found.